Acute coronary syndromes with high thrombotic burden: therapeutic innovations. (18th November 2020) - Menozzi, Alberto; Caretta, Giorgio
Abstract: Antiplatelet agents represent one of the cornerstones of drug therapy for acute coronary syndromes (ACS). In the last decade, the arrival of prasugrel and ticagrelor, faster and more powerful oral platelet receptor P2Y12 inhibitors compared to clopidogrel, significantly improved platelet inhibition in patients with ACS. However, the reduction of thrombotic risk came at the cost of increased bleeding risk. Despite having similar indications, prasugrel and ticagrelor have different characteristics and methods of use, essentially due to a different design of the trials in which they have been studied. The optimal use of these antiplatelets in clinical practice should therefore be tailored in individual patients. In the acute phase of ACS with high thrombotic burden, all oral P2Y12 inhibitors have limitations, mainly due to the delay of onset of action related to oral administration. In this scenario, parenteral antiplatelet agents (glycoprotein inhibitors IIb/IIIa and cangrelor) may play a key role in case of percutaneous coronary interventions of high thrombotic coronary lesions and in the prevention of early thrombotic complications. Cangrelor, an intravenous inhibitor of the P2Y2 receptor, has peculiar pharmacokinetic and pharmacodynamic characteristics that make it particularly suitable to be used as an antiplatelet during coronary angioplasty as it achieves a rapid and powerful antiplatelet effect in patients not pretreated with oral medications, and has a favourable safety profile in relation to the bleeding risk.